Family members' experience with in-hospital health care after severe traumatic brain injury: a national multicentre study - Unn Sollid Manskow; Cathrine Arntzen; Elin Damsgård; Mary Braine; Solrun Sigurdardottir; Nada Andelic; Cecilie Røe; Audny Anke (BMC, 2018)
Abstract Background Family member's experience and satisfaction of health care in the acute care and in-patient rehabilitation are important indicators of the quality of health care services provided to patients with severe traumatic brain injury (TBI). The objective was to assess family members' experience of the health care provided in-hospital to patients with severe TBI, to relate experiences to family member and patient demographics, patients' function and rehabilitation pathways. Methods Prospective national multicentre study of 122 family members of patients with severe TBI. The family experience of care questionnaire in severe traumatic brain injury (FECQ-TBI) was applied. Independent sample t-tests or analysis of variance (ANOVA) were used to compare the means between 2 or more groups. Paired samples t-tests were used to investigate differences between experience in the acute and rehabilitation phases. Results Best family members` experience were found regarding information during the acute phase, poorest scores were related to discharge. A significantly better care experience was reported in the acute phase compared with the rehabilitation phase (p < 0.05). Worst family members` experience was related to information about consequences of the injury. Patient's dependency level (p < 0.05) and transferral to non-specialized rehabilitation were related to a worse family members` experience (p < 0.01). Conclusions This study underscores the need of better information to family members of patients with severe TBI in the rehabilitation as well as the discharge phase. The results may be important to improve the services provided to family members and individuals with severe TBI.